Determinants of dietary diversity and drivers of food choice among low-income consumers in urban Kenya, Malawi and Zimbabwe - Gichohi-Wainaina, Wanjiku N.; Kee-Tui, Sabine Homann; Zoethout, Manon; Talsma, Elise F.; Edel, Immaculate; Hauser, Michael (Wiley, 2023)
Rapid urbanisation affects lifestyle and eating habits, predominantly causing a dietary shift that adds challenges to meet dietary recommendations within a complex food system. This research investigated dietary diversity and food choice drivers among low‐income consumers in three urban settlements (Nairobi, Kenya; Bulawayo, Zimbabwe and Lilongwe, Malawi, representing rapid, moderate and slow urban growth patterns, respectively) as a first step towards improving diets across cultures and geographies.Mixed methods data collection was employed for this study. Qualitative methods such as rapid foodscape appraisal workshops and food stories in selected low‐income settlements in Nairobi, Bulawayo and Lilongwe were utilised to collect information on the food environments (food balances, infrastructure, safety, policies and institutions). Quantitative data such as socio‐demographic characteristics and dietary diversity were collected via structured questionnaires using Cognitive Edge's SenseMaker® (n = 890, 450 and 440 for Nairobi, Bulawayo and Lilongwe, respectively). The dietary intake of respondents was assessed using a 24‐h recall, which was then converted to the food group diversity score (FGDS).Different levels of compounded stress affected dietary diversity and quality, including high food prices, concerns about sanitation and hygiene and the role of food standards regulation bodies. The mean FGDS across all locations was lower than the recommended cut‐off of 5 (4.5, 2.8 and 2.6 across Nairobi, Zimbabwe and Lilongwe, respectively). Additionally, in Nairobi, there were gender differences in diet diversity, with men having a higher dietary diversity score than women (4.6% vs. 4.3%; p = 0.004). The majority of respondents in Lilongwe (65%) reported price as the most important driver of food choice, compared to 38% in Nairobi and 42% in Bulawayo.Our observation of poor‐quality diets provides further evidence of the need for food policies that are cognisant of the nutrition and health of the growing population of the urban poor. Such policies would focus on lowering the costs of nutritious foods as well as ensuring food safety within the complex food system observed in the urban low‐income environment.